Serum autoantibodies directed against transglutaminase-2 have a low avidity compared with alloantibodies against gliadin in coeliac disease. (9th June 2014) - Gelderman, K A; Drop, A C A D; Trouw, L A; Bontkes, H J; Bouma, G; van Hoogstraten, I M W; von Blomberg, B M E
Summary: Coeliac disease is characterized by intolerance to gliadin and related gluten components present in wheat, barley and rye. Coeliac disease patients harbour antibodies directed against alloantigens such as gliadin, but also against the autoantigen transglutaminase-2 (TG2). The type and quality of antibody responses provides insight into the underlying immune activation processes. Therefore, in this study we have analysed the avidity of the antibody response directed against the autoantigen TG2 and compared this with antibody responses against the alloantigens gliadin and Escherichia coli . We observed that the immunoglobulin (Ig)A autoantibody response directed against TG2 is of low avidity compared with the IgA response against the alloantigens gliadin and E. coli in the same patients; the same was true for IgG, both in IgA-deficient and in -sufficient coeliac patients. The observed avidities appear not to be related to disease stage, antibody levels, age or duration of exposure to gluten. In conclusion, in coeliac disease there is a clear difference in avidity of the antibody responses directed against the auto- and alloantigens, indicating different regulation or site of initiation of these responses.